'A man can only be truly known in drunkenness and war.' An anthropological perspective on alcohol use during the Portuguese Colonial War. (31st May 2021) - Gil Calado, Vasco
Abstract: Background and aim: To understand the use of psychoactive substances, one must consider the context and the social circumstances in which the substance use occurs. This paper discusses alcohol use from a socio‐cultural perspective, based on the use of alcoholic beverages among the Portuguese servicemen who fought in the Portuguese Colonial War (1961–74). Method: In‐depth interviews were carried out with 17 former Portuguese soldiers. Simultaneously, extensive bibliographic and documentary research was carried out based on a broad set of biographical and autobiographical texts by former military personnel. Finally, an on‐line survey ( n  = 210) was conducted among ex‐combatants of the Portuguese Colonial War. Results: Alcohol drinking among Portuguese servicemen was high during the Portuguese Colonial War. Socio‐cultural factors (such as regarding alcohol consumption as therapeutic and affirming masculinity) explain why alcohol drinking was so intense and frequent, and why repeated drunken behaviour was tolerated and undervalued by the military authorities, who considered it normal and not a health problem or disorder. Conclusion: The use of alcohol in the Portuguese Colonial War is an empirical example of how what is considered 'acceptable', 'normal' or 'pathological' may depend more on socio‐cultural norms than on objective and measurable criteria, including clinical criteria.